2019
DOI: 10.4236/ojfd.2019.91003
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Centrifugal Compressor for Micro Gas Turbine: Investigation of Scaling and Tip Clearance Effects

Abstract: The aim of this paper is to investigate the design in similarity of a centrifugal compressor for micro gas turbine and the related scaling effects on performance using CFD investigations. This work is part of a research project carried out by the Department DIME of the University of Genova, with the purpose of investigating the performance of a micro gas turbine in the change from 100 kW electrical output to 250 kW, while maintaining the compressor pressure ratio and geometry in similarity. The first part of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…radial compressor and turbine, is presented. The procedure is based upon the design criteria developed and explained in detail in several papers developed by the authors for lower net power machines: in particular, the overall cycle design is presented in Barsi et al [11], while the detailed design for turbine and compressor are reported in Perrone et al [12] and Barsi et al [13], respectively. In this paper, the main results and overall performance obtained by the procedure, taking into account the scaling criteria analysed in Cumpsty [14], are presented.…”
Section: Gas Turbine Designmentioning
confidence: 99%
“…radial compressor and turbine, is presented. The procedure is based upon the design criteria developed and explained in detail in several papers developed by the authors for lower net power machines: in particular, the overall cycle design is presented in Barsi et al [11], while the detailed design for turbine and compressor are reported in Perrone et al [12] and Barsi et al [13], respectively. In this paper, the main results and overall performance obtained by the procedure, taking into account the scaling criteria analysed in Cumpsty [14], are presented.…”
Section: Gas Turbine Designmentioning
confidence: 99%